Organizing the national prostate cancer audit in the UK (review of foreign literature) - D. A. Andreev (Onkourologiâ, 2021)
Background. The growing number of patients with prostate cancer (PCa) imposes additional requirements on the quality control system in healthcare, including ensuring the widespread availability of innovative algorithms for early diagnosis and treatment. One illustrative example of quality management initiatives is national PCa audit in the UK. Objective. Highlighting the approaches to quality assessments within audit of PCa care in the UK.Materials and methods. The relevant scientific data have been retrieved from Google and PubMed. The search horizon covered the last 10 years. The queries included such wording as: "prostate cancer" AND "audit" OR/AND "Great Britain" AND "quality assurance", etc.Results. At least four basic parameters were used as signal indicators to check the consistency and overall quality of the collected data on PCa patients in England and Wales. The fundamental arrangement of clinical quality indicators for PCa care comprised not less than fourteen measures. The outliers for some indicators were allocated into two groups using such criteria as: 1) more than three standard deviations from the national average (definition of an alarm); 2) more than two but below three standard deviations from the national average (definition of an alert). The outlier policy is usually applied for three treatment outcome performance indicators.Conclusion. The multidisciplinary teams must actively collaborate to provide the best standards of cancer care to the community. The introduction of multicriterial assessments to monitor the performance of highly specialized professional groups would bring a great benefit for cancer patients, particularly, through increasing the affordability of state-of-the-art medical algorithms across the counties.